Thrombin immobilized hemocompatible radiopaque polyurethane microspheres for topical blood coagulation - Naik, Sonali S.; Torris, Arun; Ghuge, Gorakh Hiraman; Karthika, V. K.; Joseph, Roy; Nair, Kiran Sukumaran (JOURNAL OF BIOMEDICAL MATERIALS RESEARCH PART A, 2025)
Keywords: ALGINATE MICROSPHERES; ENDOVASCULAR TREATMENT; PRECISE LOCALIZATION

Triple G-C-T base-coded nucleobase self-assembling monomers featuring polymerizable groups for 3D printing - Gawande, Akshay J.; Kamble, Ganesh N.; Singh, Dharmendra; Sanjayan, Gangadhar. J.; Nair, Kiran Sukumaran (ACS Applied Polymer Materials, 2025)
Self-assembling monomers (SAMs) offer a versatile strategy for enhancing the performance of photoresins in Digital Light Processing (DLP) 3D printing. In this work, we report the design and synthesis of two photoprintable, nucleobase-inspired SAMs featuring a triple G-C-T base-coded hydrogen-bonding motif. This SAM was formulated using 2-hydroxyethyl acrylate (2-HEA), 1,6-hexanediol diacrylate (HDDA), and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) to prepare UV-curable resins suitable for high-resolution DLP printing. Remarkably, the printed samples exhibited supramolecular self-assembly, facilitated by dynamic hydrogen bonding, demonstrating a notable enhancement in thermal and mechanical performance when compared to the control sample. Thermal properties evaluated by a differential scanning calorimeter revealed an increase in the glass transition temperature (T-g) from 15 degrees C to 54 degrees C for SAM-incorporated printed materials. Mechanical testing demonstrated a >200% increase in toughness and >150% improvement in tensile strength relative to the unmodified resin while maintaining or exceeding the original elongation at break (up to similar to 74%). Variable-temperature FTIR spectroscopy confirmed the presence of thermally responsive supramolecular interactions. Notably, self-healing behavior was observed in both GCT-A 15 wt % and GCT-S 15 wt % formulations, indicating partial recovery of mechanical integrity under mild thermal conditions due to reversible hydrogen bonding. These findings demonstrate the potential of SAMs as functional additives for developing robust, thermally stable, and self-healing DLP-printed materials for advanced engineering applications.
Keywords: 3D printing; hydrogen bonding; Self-assembly; Self-healing; Triple G-C-T nucleobase

Triple G-C-T base-coded self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications - Singh, Dharmendra; Gone, Nilu V.; Bandi, Kiran; Davis, Disiya; Nair, Kiran Sukumaran; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2025)
We report self-assembling water-soluble nucleobase monomers with a broad scope for biomaterial and protein bioconjugation applications. These nucleobase monomers are adorned with nature-inspired triple G-C-T nucleobases featuring three recognition sites: DDA (G mimic), DAA (C mimic), and ADA (T mimic). Using readily accessible starting materials, these monomers can be synthesized in excellent yields, making them good choices for diverse applications. Their unique structural features, coupled with their water solubility, may offer exciting opportunities for the creation of new biomaterials.